PkCOs: synchronisation of packet-coupled oscillators in blast wave monitoring networks - Zong, Yan; Dai, Xuewu; Gao, Shang; Canyelles-Pericas, Pep; Liu, Shuxin (IEEE, 2021)
Blast waves with a large amount of energy, from the use of explosive weapons, is a major cause of traumatic brain injury in armed and security forces. The monitoring of blast waves is required for defence and civil applications. The utilisation of wireless sensing technology to monitor blast waves has shown great advantages such as easy deployment and flexibility. However, due to drifting embedded clock frequency, the establishment of a common timescale among distributed blast monitoring sensors has been a challenge, which may lead to a network failing to estimate the precise acoustic source location. This work adopts a Packet-Coupled Oscillators (PkCOs) protocol to synchronise drifting clocks in a wireless blast wave monitoring network. In order to address packet collisions caused by the concurrent transmission, an anti-phase synchronisation solution is utilised to maintain clock synchronisation, and the corresponding superframe structure is developed to allow the hybrid transmission of the Sync packet and the blast wave monitoring data. As a network scales up and the hop distance grows, the packet exchange lag increases during a superframe. This, along with the drifting clock frequency, leads to the degradation of synchronisation performance while the clock frequency is usually assumed to be zero and non-drifting. Thus, a compensation strategy is proposed to eliminate the joint impacts and to improve the synchronisation precision. The theoretical performance analysis of the PkCOs algorithm in the network is presented along with verification by simulation means. Finally, the performance of the PkCOs synchronisation protocol is evaluated on an IEEE 802.15.4 hardware testbed. The experimental results show that the PkCOs algorithm provides an alternative clock synchronisation solution for blast wave monitoring networks.
Keywords: Time synchronisation; packet-coupled oscillators (PkCOs); pulse-coupled oscillators (PCO); anti-phase synchronisation; desynchronisation